Dip n’ Drench / Auni Ramani … [et al.]. - Ramani, Auni; Mohd Nizam, Nazhatul Hana; Nik Hassan, Nik Farrah Nasuha; Sahidin, Nora Safia; Jeffry, Nur Adiba Hasana
Dip n’ Drench company is a company that offers the best pickles condiments (dip and salad dressing sauce) with unique and better taste to our beloved consumers. It is target to provide satisfaction with high quality in line with our vision and mission in order to compete with other brands in this Food Industry. Our top products, consists of The OG! (original) and Don’t Sweat It! (spicy) will be highlighted in this business plan as our main product under Dip n’ Drench company. We ensure that this pickle condiment will not only famous among pickles lovers but only people who want to practice healthy lifestyle as our product comes with many nutrition at affordable price. Our business is run by five important figures namely General Manager, Human Resource Manager, Financial Manager Marketing Manager and Production and Quality Manager. All of these figures hold a critical role in our organization in order to achieve our objectives in this business path. As for the marketing plan, we decided to choose some strategic place to build our factory and branches as well as we prepared with many marketing strategies to ensure this business is run smoothly. We are planning to sharpen our operational plan to increase the sales of Dip n’Drench products as many consumers may be able to buy products once itis famous. We believe and motivated that with this business plan, our business may reach to a higher level and become a well-known brand in Malaysia and abroad.